Winning Connections? : Special Interests and the Sale of Failed Banks - Igan, Deniz (IMF Working Papers; Working Paper, 2017)
We study how lobbying affects the resolution of failed banks, using a sample of FDIC auctions between 2007 and 2014. We show that bidding banks that lobby regulators have a higher probability of winning an auction. In addition, the FDIC incurs higher costs in such auctions, amounting to 16.4 percent of the total resolution losses. We also find that lobbying winners have worse operating and stock market performance than their non-lobbying counterparts, suggesting that lobbying results in a less efficient allocation of failed banks. Our results provide new insights into the bank resolution process and the role of special interests.